Potencial de produção de leite de cabras Saanen utilizando gordura protegida nas dietas - Souza, Rodrigo de (2012)
The objective was to evaluate the use of bypass fat to increase energy level in diet of Saanen goats and its effects on body weight, dry matter intake (DMI), food digestibility, feed efficiency (FE), lactation curves, economic evaluation and milk quality. Twenty Saanen goats (± 60.0 kg) were distributed in a completely randomized design in four treatments using the following energy levels in diets: 2.6 Mcal of metabolizable energy per kg of dry matter (Mcal ME/kg DM) - without bypass fat and 2.7; 2.8 and 2.9 Mcal ME/kg DM - with bypass fat as calcium salts of long chain fatty acids (Lactoplus®). The roughage:concentrate used was 60.0% of corn silage and 40.0% of concentrate. Experimental period was composed of 21 days before partum until 180 days of lactation and goats were confined in individual stalls and milked twice daily. Lactation curves were obtained by dairy weighing of milk production and DMI by diet fed and orts. The economic evaluation of diets was made based on DMI and lactation performance. Goats were weighted weekly to obtain body weight variation. The marker used to estimate the digestibility of dry matter and nutrients was indigestible neutral detergent fiber. Milk quality was evaluated making monthly collect and analyzing the composition and somatic cell count, as well as fatty acid profile of milk fat, which was evaluated in three periods. Fat supplementation raised intake of total digestible nutrients of diets and did not affect the fiber digestibility, did not limited DMI, and also did not change in body weight. Fat supplementation altered the lactation curve, promoting lactation peak later and with greater persistence, which resulted in an increase in total milk production, with better productive results with 2.85 Mcal and better economic results with 2.7 Mcal. Bypass fat supplementation increased fat and lactose in milk, but it was observed a decrease in protein content of milk. The fatty acid profile of milk fat was influenced by diet, with higher levels of long chain fatty acids and polyunsaturated fatty acids, with the addition of dietary fat. Raising the level of dietary energy for Saanen goats up to 2.9 Mcal/kg DM, using bypass fat, has no effect on body weight, does not limit dry matter intake, allows a higher intake of total digestible nutrients, changes the lactation curve and favors the milk production with higher content of fat, with beneficial properties for human health. The most productive response is observed with 2.85 Mcal/kg DM, and the best economic results are observed with 2.7 Mcal ME/kg DM.